The Role of Islamic Principles in The Development of Accounting - Sumidartiny, Ai Netty; Safitry, Martina (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2025)
The development of modern accounting has been influenced by various value systems and traditions, one of which is Islamic teachings. Islam makes an important contribution to the development of accounting, especially through the principles of ethics, transparency and justice taken from the Koran and Hadith. Principles such as honesty, social responsibility, avoidance of riba (interest), and gharar (uncertainty) are the basis for fair recording and reporting of financial transactions. This research aims to explore how Islam contributes to the development of accounting science. This research method uses qualitative, namely using library research using the Google Scholar database to search for relevant sources. The research results show that Islamic values in the development of accounting have a definite influence on principles that emphasize contracts or transactions that are in accordance with sharia principles, which are not emphasized in conventional accounting. And sharia accounting emphasizes the spirit of Islam in Al-Baqarah verse 282, accounting in Islam has the principles of justice, truth and accountability. The formation of an organization called the Indonesian Accounting Association (IAI) on December 23 1957 and the formation of Sharia Financial Accounting Standards (SAS) were implemented as clear regulations and standardization in the practices of sharia financial institutions.